The prevalence of orthostatic hypotension and its risk factors among 40 years and above adult population in Indonesia (Faculty of Medicine Universitas Indonesia, 2004)
Factors associated with orthostatic hypotension such as age, drug induced hypotension, hypertension and diabetes mellitus have still been debatable. Most of previous studies were conducted in subjects 65 years or older, only a few were done in subjects from younger to older adults. The purpose of this study is to find the prevalence and predictor factors of orthostatic hypotension among adult population aged 40 years and above in Indonesia. This study is a part of Indonesian Hypertension Epidemiologic Survey. A random sample of 4436 subjects aged 40â94 years was obtained from various municipalities in every big island in Indonesia. Orthostatic testing, assesment of history of medical conditions (diabetes mellitus, stroke, and hypertension), blood pressure measurement and use of anti-hypertensive medications were performed. A stepwise logistic regression was used to determine the significant predictor of orthostatic hypotension. A total of 561 persons (12.6%) experienced orthostatic hypotension. Central Î±2-agonist and other centrally acting drug is the only anti hypertension medicine which influences orthostatic hypotension. Multivariate analysis showed that high systolic and diastolic blood pressures were predictor factors of orthostatic hypotension. The use of anti-hypertensive medicine was a protective factor for orthostatic hypotension. This study confirms the conclusion that age is not a predictor factor for orthostatic hypotension. In fact, the existence of comorbidities in the subjects such as hypertension (high systolic and diastolic blood pressure) is a predictor factor, while the use of anti-hypertensive medication is a protective factor. (Med J Indones 2004; 13: 180-9) Keywords: adult, orthostatic hypotension, prevalence, risk factor